Factors Affecting Health Workers Regarding Stigma of Leprosy - Hidayati, Laily; Ardianti, Elly; Nastiti, Aria Aulia (International Journal of Psychosocial Rehabilitation, 2020)
Leprosy remains a neglected disease with a strong negative stigma in society. Stigma does not only come from ordinary people, but also health workers. This study aims to determine the factors af ecting health workers regarding stigma of leprosy. This research used a cross-sectional design. A sample of 257 out of 773 health workers in 23 Public Health Center (Puskesmas) in Surabaya-Indonesia taken by cluster sampling technique. Independent variables in this research were age, gender, education, profession, length of working experience, knowledge, institutional support and informational exposure, while the dependent variable was the leprosy stigma by health workers. Data were obtained by questionnaire and analyzed by using chi-square and Spearman’s Rho. The result showed 35.4% of respondents had a high stigma. There is a relationship between sex (p = 0.002), education (p= 0.000), profession (p= 0.000), knowledge (p= 0.000), institutional support (p = 0.000), and information exposure (p = 0.000) with stigma health workers. Otherwise, age (p= 0.124) and length of working experience (p= 0.349) did not show association with the stigma of health workers. It is expected that Public Health Centers in Surabaya can provide more informational support about leprosy for the health worker to increase the knowledge and so that they can eliminate the stigma and optimize the leprosy control program.